Perancangan Aplikasi Sistem Penjualan Sembako Di Toko Erna Berbasis Java Netbeans - Amanda Guru Singa; V.H. Valentino; Rudi Prasetya (Institut Bisnis Nusantara, 2025)
The purpose of this research is to create a manual grocery sales application system into a computerized one at Erna Store so that it can be used by cashiers and owners to facilitate sales transactions, purchase goods, and print overall reports. The research method used is the Waterfall method. Where in building this system, a system design tool is used, namely UML, and uses the Java Netbeans programming language and MySQL database using XAMPP. During the research, the researcher found that in making this report there are still many shortcomings, namely the display is still less attractive and the storage media still uses paper, which causes a buildup of documents. The conclusion of this system is to make it easier for cashiers to make sales transactions, provide sales receipts, and print all transaction reports of data that have been processed by the system, making it easier and faster. With this proposed system, it is expected to make it easier for cashiers to work.